2016
DOI: 10.1039/c6ra10364b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and microstructural properties of the scaffold based on a 3-(trimethoxysilyl)propyl methacrylate–POSS hybrid towards potential tissue engineering applications

Abstract: The biomimetic organic–inorganic scaffold with the chemical composition, structural dimensions, topography, and microstructural properties that fulfills the requirements for hard-tissue engineering was developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 48 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…47,48 To date, our recent studies, reported in 5, have indicated that hexahedral organic-inorganic hybrids based on a siloxane cage-like core with eight 3-(trimethoxysilyl)propyl methacrylate side arms can be considered unique three-dimensional scaffolds that fulfil potential hard-tissue-engineering requirements realized by multiple factors such as the chemical composition, structural dimensions, topography, and microstructural properties. 34 Our investigations also prove that the methacrylate derivatives used, not only those attached to the Si 8 O 12 cage, are safe components and constitute efficient reservoirs for osteoblasts. 42 For this reason, they may be used in future experiments, as they do not have any toxic influence on cells.…”
Section: Poss-based Biomaterials Containing Methacrylatederived Sidesupporting
confidence: 58%
See 3 more Smart Citations
“…47,48 To date, our recent studies, reported in 5, have indicated that hexahedral organic-inorganic hybrids based on a siloxane cage-like core with eight 3-(trimethoxysilyl)propyl methacrylate side arms can be considered unique three-dimensional scaffolds that fulfil potential hard-tissue-engineering requirements realized by multiple factors such as the chemical composition, structural dimensions, topography, and microstructural properties. 34 Our investigations also prove that the methacrylate derivatives used, not only those attached to the Si 8 O 12 cage, are safe components and constitute efficient reservoirs for osteoblasts. 42 For this reason, they may be used in future experiments, as they do not have any toxic influence on cells.…”
Section: Poss-based Biomaterials Containing Methacrylatederived Sidesupporting
confidence: 58%
“…[31][32][33] Recently, we have reported on the synthesis of biohybrids based on the 3-(trimethoxysilyl)propyl methacrylate-POSS compound. 34 Inspired by those studies, spherosilicate 2 was functionalized in this work by (2-hydroxyethyl)methacrylate (HEMA) and ethylene glycol dimethacrylate (EGDMA) monomers giving [OAS-POSS-NH]HEMA (3) and [OAS-POSS-NH]EGDMA (4), respectively. These organic monomers were used because they constitute commonly applied agents in medical biomaterials.…”
Section: Synthesis and Characterization Of Fully Functionalized Methamentioning
confidence: 99%
See 2 more Smart Citations
“…Micro-CT can be used to investigate completely (over the entire adhesive volume) and accurately the width of the dental adhesive layer, as also demonstrated in this work. It can detect microleakage areas generated by gaps between the tooth interface and the composite filling material, as approached in numerous studies [69][70][71]. Nowadays, a requirement of dental research is to analyze samples in a non-destructive manner.…”
Section: Comparison Between Optical Microscopy and Micro-ct Resultsmentioning
confidence: 99%